Perceptual Sensitivity of Psychogenic Nonepileptic Seizure (PNES) Patients - Singh, Priyesh Kumar (International Journal of Epilepsy, 2025)
Aim The aim of the present study was assess the perceptual sensitivity of psychogenic nonepileptic seizure (PNES) patients. Secondarily, we also aimed to replicate previous findings and explore whether PNES patients exhibit tendencies of preattentiveness in response to unpleasant stimulus.Materials and Methods A total of 56 individuals were selected for the present research, from which 28 were PNES patients and 28 healthy individuals. A 2 × 3 design was used for the present study. The emotional-N-back paradigm was used for presenting stimuli. Perceptual sensitivity (d') was calculated on the basis of hits and false positives.Result The result of analysis of variance (ANOVA) showed significant distinction between PNES and healthy individuals on perceptual sensitivity (d') measure (F(1, 50) = 19.11, p = 0.000). Similarly, result of ANOVA (F(2, 100) = 63.64, p = 0.000) for within-group valence showed a significant difference between pleasant, unpleasant, and neutral stimuli among PNES and healthy individuals ensuring a clear distinction between them.Conclusion These findings suggest a notable disparity in perceptual sensitivity between PNES and healthy individuals, supporting the notion that individual with PNES experience emotional disturbance and possess a dysfunctional cognitive-affective system. Moreover, the result lends credence to the hypothesis that PNES patients are more responsive to unpleasant emotions than to pleasant or neutral ones.
Keywords: PNES; perceptual sensitivity; valence; pathology; IAPS